An XML-based Quality of Service Enabling Language for the Web - GU, XIAOHUI; NAHRSTEDT, KLARA; YUAN, WANGHONG; WICHADAKUL, DUANGDAO; XU, DONGYAN (Journal of visual languages and computing, 2002)
In this paper, we introduce an XML-based hierarchical QoS markup language, called HQML, to enhance distributed multimedia applications on the World Wide Web (WWW) with quality of service (QoS) capability. The design ofHQML is based on two observations: (1) the absence of a systematic QoS specification language, that can be used by distributed multimedia applications on the WWW to utilize the state-of-the-art QoS management technology and (2) the power and popularity of XML to deliver richly structured contents over the Web. HQML allows distributed multimedia applications to specify all kinds of application-specific QoS policies and requirements. During runtime, the HQML Executor translates the HQML file into desired data structures and cooperates with the QoS proxies that assist applications in end-to-end QoS negotiation, setup and enforcement. In order to make QoS services tailored toward user preferences and meet the challenges of uncertainty in the distributed heterogeneous environments, the design of HQML is featured as interactive andflexible . In order to allow application developers to create HQML specifications correctly and easily, we have designed and developed a unified visual QoS programming environment, called QoSTalk. In QoSTalk, we adopt a grammatical approach to perform consistency check on the visual QoS specifications and generate HQML files automatically. Finally, we introduce the distributed QoS compiler, which performs the automatic mappings between application- and resource-level QoS parameters to relieve the application developer of the burden of dealing with low-level QoS specifications.